Assessing Borneo’s tropical forests and plantations: a multi-sensor remote sensing and geospatial MCDA approach to environmental sustainability - Suab, Stanley Anak; Supe, Hitesh; Louw, Albertus Stephanus; Korom, Alexius; Rakib, Mohd Rashid Mohd; Wong, Yong Bin; Kemarau, Ricky Anak; Avtar, Ram (Frontiers in Forests and Global Change, 2024)
The assessment of environmental sustainability is of utmost importance for the forests and plantations in Borneo, given the critical need for environmental protection through identification and mitigation of potential risk. This study was conducted to assess the environmental sustainability of tropical forest and plantations landscape, a case study in northern Sabah, Malaysian Borneo. Applications of the latest high-resolution multi-sensor remote sensing and geospatial MCDA are cost-effective and useful for large-scale environmental sustainability assessment. The Land use land cover (LULC) of the study area was mapped with synergistic use of Sentinel-1 Synthetic Aperture Radar (SAR), Sentinel-2 optical and high-resolution PlanetScope satellite imageries resulting in overall accuracy of 87.24%. Five sustainability indictor layers: slope protection, riparian reserve, landscape connectivity and quality, high conservation value (HCV) and water turbidity were developed from the LULC map, ancillary datasets of SRTM and forest operation basemap with reference to standards from Environment Protection Department (EPD), Roundtable on Sustainable Palm Oil (RSPO) and Forest Management Plan (FMP) for the analysis using Multi Criteria Decision Analysis (MCDA) model. The results revealed that overall, the study areas are in the high sustainability category at 61%, medium 31% and only 8% in low category. We analysed the environmental sustainability of five land uses boundaries and results shown that Industrial Tree Plantations (ITP) and Village Reserve are mostly in high category. Meanwhile oil palm plantations, Rubber plantations and Forest Reserve (FR) are the majority in medium category. Both oil palm and Assessing Borneo's tropical forests and plantations: A multi-sensor remote sensing and geospatial MCDA approach to environmental sustainability 2 rubber plantations are majority in medium class due to monocropping land use type having low in the landscape connectivity and quality individual sustainability indicator layer. The study presented the concept of use of multi-sensor remote sensing for LULC mapping with geospatial MCDA for environmental sustainability assessment useful to stakeholders for improving the management plan also contributing towards the progress of achieving UNSDGs and addressing REDD+.